Augmented Reality-Based Science Learning Design on Human Respiratory System for Elementary Students - Eliya Rochmah; Vina Siti Alifah; Dewi Yulianawati (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of digital technology in the world of education is increasingly advancing. The rampant use of technology in learning encourages innovation in technology-based learning media. One of them is the use of augmented reality technology in learning IPAS material on the human respiratory system. This research uses descriptive qualitative methods. This research describes, analyzes, and provides an in-depth explanation regarding the design of IPAS learning on the human respiratory system material based on Augmented Reality in elementary schools. The location of this research was conducted at SD Negeri 1 Terusan with participants being class teachers and fifth-grade students. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study indicate that learning planning includes the design of teaching modules by selecting appropriate learning media for the respiratory system material, namely augmented reality media that is integrated into the steps of the discovery learning model, resulting in an increase in conceptual understanding and clear visualization of the material. The renewal of this research is that in this study, the researcher integrates augmented reality media with the learning model used in the human respiratory system material in the fifth grade. Based on the research that has been conducted, it is necessary to design optimal learning so that learning runs well; in addition, the use of augmented reality media in the respiratory system material can facilitate students in understanding the concept of the material and create interactive learning that is in line with the times.